Psychophysiological correlates of science communicators - David Vagni; Gennaro Tartarisco; Simona Campisi; Loredana Cerbara; Marco Dedola; Alessandra Pedranghelu; Alexandra Castello; Francesca Gorini; Chiara Failla; Marco Tullio Liuzza; Antonio Tintori; Giovanni Pioggia; et al. (PLoS ONE, 2025)
We conducted a study in an ecological setting to evaluate the heart rate variability (HRV) of expert communicators during a live national primetime video interview. The study involved 32 expert science communicators, all with mid- to long-term experience in public speaking and outreach work, who were evaluated by an external jury to assess their communication skills. Prior to the experiment, participants completed an online survey to gather socio-demographic data, work-related information, and psychological profiles. The six indices of communication abilities assessed by jury were: Interest, Agreement, Engagement, Authoritativeness learning, and Clarity. HRV acquisitions were divided into three phases: baseline pre-interview, during the interview, and another baseline recording after the interview. Science communicators were characterized by high levels of self-esteem and prosociality, which were positively correlated with communication indices and inversely correlated with age. Evaluation of physiological responses showed that the total power and low-frequency components of HRV were significantly higher in the post-interview phase compared to both the interview and pre-interview phases. However, when we divided the entire group according to high and low Authoritativeness and Clarity indices, significant interactive effects were detected. Indeed, for the low Authoritativeness and Clarity subgroups, significant differences among all phases were observed, with total power decreasing from the pre-interview to the interview phase and increasing in the post-interview phase. This indicates a clear pattern of stress response and recovery. In contrast, the high Authoritativeness and Clarity subgroup showed less variation across phases, suggesting better stress regulation or less perceived stress during the interview. We provided the psychophysiological basis of science communication expertise that can affect the control of stress regulation during public speaking.